The Use of FBC Fly Ash in the Preparation of Portland Cement Clinker - Kulisek, Karel; Gazdic, Dominik; Dvorak, Karel; Fridrichova, Marcela (Key Engineering Materials, 2016)
The present work focuses on the use of fluid fly ash for Portland clinker burning. Fluid ashes are carriers of all basic oxides represented in the cement raw meal. However, while the share of hydraulic oxides is in ashes sufficient, there is a significant deficiency in calcium oxide content. Preliminary studies have shown that the combination thereof with calcite as the second essential component of the fluid fly-ashes for the raw material based on Portland clinker burning application, it is necessary to solve a problematic issues. The first one concerns the potential leakage SOx resulting from decomposition of CaSO4 ash into the atmosphere. The second circumstance is the correction tracks raw meal in order to redistribute in the samples prepared under the initial studies, the obtained clinker minerals content in favor of calcium silicate, of them further in favor of alite. The last issue is the evaluation of the impact of fluid utilization of fly ash as a partial raw material bases for reducing CO2 emissions in the Portland clinker burning.